Stability of a dynamical system related to XY-Model in Quantum Markov Chains Scheme - Mukhamedov, Farrukh; Saburov, Mansoor (Institut Matematik Kejuruteraan, Universiti Malaysia Perlis, 2010)
In the present paper we studied stability of the dynamical system which is related to XY-model in quantum Markov chains scheme on Cayley tree of order three. We found out all fixed points and showed an absence of periodic points. We studied the asymptotical behavior of the trajectory of the dynamical system.